Analisis Putusan Nomor 833/Pdt.G/2022/Pa.Bn tentang Hak Asuh Anak yang Belum Mumayyiz karena Ibu Murtad Perspektif Maqashid Syariah - Sirajuddin, Sirajuddin; Fahima, Iim; Fadila, Aziyaty (UIN Fatmawati Sukarno Bengkulu, 2023)
Abstrac: The formulation of the problem in this research is: 1) What is the basis for the judge's considerations in the religious court decision regarding child custody in decision number 833/Pdt/G/2022/Pa.Bn?. 2) What is the analysis of decision number 833/Pdt/G/2022/Pa.Bn regarding child custody in positive law? 3) What is the analysis of decision number 833/Pdt/G/2022/Pa.Bn regarding child custody from a maqashid sharia perspective ?. The type of research used in this paper is library research using a case approach. This research concludes: 1) In decision No.833/Pdt.G/2022/PA.Bn the panel of judges rejected the plaintiff's decision saying that in their consideration it was in the best interests of the future of the Plaintiff and Defendant's child to remain under the care of the Plaintiff and Defendant until the child reached the age of 12 years old / can decide for himself who he wants to join, if this decision is rejected, the next problem will be that the child will still be fought over by his parents. 2) Positive legal analysis of this decision. The Child Protection Law does not clearly state who the party has the right to care for. the child if a divorce occurs, whether for the husband or wife, then Law No. 23 of 2002 concerning Child Protection article 33 paragraph (3) reads: